Pulmonary rehabilitation in Africa (community-driven citizen science approach): (a focus on COPD in low-resourced communities in South Africa) - Isiagi, Moses (Department of Medicine, 2025)
Chronic Obstructive Pulmonary Disease (COPD) represents a significant global health challenge, particularly in low-and middle-income countries (LMICs), especially in Africa. Pulmonary rehabilitation (PR) is a well-established intervention to address COPD in High income countries (HICs) and has been incorporated into the healthcare systems in many settings. However, its implementation and population-level delivery in Africa are almost non-existent. This dissertation explored COPD management and PR services in low-resourced African settings, specifically focusing on a disadvantaged peri-urban community in South Africa. The study utilized a 3-pronged approach which we believe holds significant potential to investigate and perhaps, address these challenges. The purpose of this study was to examine the current state of PR services in low-resourced settings in LMICs, evaluate healthcare providers' clinical awareness and support in Africa, and explore COPD risk perceptions and prevention preference in the study setting. In addition, the study utilizes the findings and lessons learnt to support the development of community-driven PR implementation strategies in the disadvantaged African setting using a participatory approach. Methods: The methodology encompassed three distinct components: First, a systematic review was conducted to gain understanding and map the landscape of home-based and community-based PR programmes in low-resourced African settings registered with PROSPERO (CRD42023480324). Second, a cross-sectional virtual electronic survey was administered between January and March 2020, targeting African clinicians with Pan-African Thoracic Society and South African Thoracic Society networks. Finally, a participatory community-based Citizen science project was implemented in the Klipfontein health district, incorporating focus group discussions, Citizen science interviews, and advocacy workshops. Results: The study revealed a significant gap in research regarding PR programmes in African settings, with no published studies comparing home-based and community-based PR delivery models in the region. The closest relevant research was a Brazilian protocol for home-based cardiac rehabilitation. However, the survey of healthcare professionals from 23 countries demonstrated awareness and recognition of PR as an effective intervention for COPD. Despite significant implementation challenges, over 85% of the surveyed healthcare professionals expressed confidence in PR programmes' ability to improve symptoms and reduce patient exacerbation. Insights from Citizen science indicate limited community awareness of COPD, often confused with general respiratory conditions like asthma. Discussions and EpiCollect findings show that while communities recognize risk factors such as smoking and environmental exposure, there is a pressing need for targeted education about COPD before effectively implementing PR interventions. Furthermore, participants in the study were willing to participate in a community-driven PR intervention and listed important strategies that would make this intervention accessible, acceptable, and sustainable. Conclusion: This study presents a novel approach to COPD risk perception and PR implementation in resource-limited settings. The need for pulmonary rehabilitation is well documented and understood at a scientific and specialist pulmonologist level. Local logistics, training, funding, and staffing challenges hindered the implementation. Community-based "out-of-hospital" PR programmes are well-described in high-income countries. However, they are almost non- existent in low-income settings. At the patient level, the lack of awareness of the diagnosis, understanding and access to treatment may inadvertently be the most important factor limiting the access of patients with COPD to an effective PR intervention. While traditional 'medical science' methods have been instrumental in increasing access to PR in low-income settings, the potential of a more Citizen science approach with engagement at the community level with healthcare staff, patients, and community members is promising. This approach may facilitate the development and implementation of a better multilayered and acceptable programme to those who need it most (the vulnerable population in disadvantaged communities in Africa), offering hope for the future of COPD management in Africa.